2012
DOI: 10.1364/oe.20.005518
|View full text |Cite
|
Sign up to set email alerts
|

Silicon photodiodes with high photoconductive gain at room temperature

Abstract: Silicon photodiodes with high photoconductive gain are demonstrated. The photodiodes are fabricated in a complementary metal-oxide-semiconductor (CMOS)-compatible process. The typical room temperature responsivity at 940 nm is >20 A/W and the dark current density is ≈ 100 nA/cm2 at 5 V reverse bias, yielding a detectivity of ≈ 10(14) Jones. These photodiodes are good candidates for applications that require high detection sensitivity and low bias operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…A comparison can be made with Si photodiodes fabricated by Li et al 54 using high quality float zone Si substrates. The typical rise and fall times of 0.55 and 0.3 ms were obtained in this device, respectively.…”
mentioning
confidence: 99%
“…A comparison can be made with Si photodiodes fabricated by Li et al 54 using high quality float zone Si substrates. The typical rise and fall times of 0.55 and 0.3 ms were obtained in this device, respectively.…”
mentioning
confidence: 99%
“…In comparison with the commercial Si and Ge photodetectors (the solid lines in Figure ) at −12 V, approximately three orders of magnitude higher responsivity was achieved at the comparable bias. Furthermore, the responsivity for the b‐Si photodetector was over 10 times higher than that of previously reported results of b‐Si photodetectors . The two insets in Figure show the highest response and infrared photoresponse against the reverse bias, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…By considering the dark current as the major noise, the specific detectivity ( D *) of the photodetector can be calculated as D= A1/2R2eIdark1/2 where A is the device working area, R is the responsivity, e is the electron charge constant, and I dark is the dark current. At −5 V bias, the specific detectivity showed a value of 1.22 × 10 14 Jones (1 Jones = 1 cm Hz 1/2 W −1 ) at 1080 nm at room temperature, indicating a much higher sensitivity of photon detection than the commercial silicon photodetector and previously reported results . Based on the low dark current and the large difference between the dark current and photocurrent, b‐Si photodetectors exhibit great potential in detection, with a high photon sensitivity and responsivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hyperdoping in silicon has been recognized to be a potential for the fabrication of silicon‐based photodetectors . It has been reported that the chalcogen hyperdoped silicon photodetector can exhibit a high photoconductive gain under illumination while preserve a diode‐rectifying effect in the dark . This provides a novel path to the silicon‐based photoconductors with a low noise and a high detect sensitivity.…”
mentioning
confidence: 99%